2006
DOI: 10.1080/03014460600909372
|View full text |Cite
|
Sign up to set email alerts
|

Age of puberty in Iranian girls living in Tehran

Abstract: The aim of this study was to determine the age of appearance of secondary sexual characteristics in Iranian girls living in Tehran. A cross-sectional study was conducted between 2003 and 2004 on 1420 6-17-year-old females in different parts of Tehran. Data were collected on the basis of a multistage probability sampling. Secondary sexual characteristics were evaluated by inspection and palpation, and were recorded according to Tanner staging. The subjects were asked about the occurrence of menarche and the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
4
14
0
2
Order By: Relevance
“…We used the 3rd percentile which is close to the usual cut-off measure of -2SD. In our study, the 3rd percentile for B2 is close to that reported by Razzaghi-Azar et al in Tehran, [7] and the age of precocious puberty is also very close to theirs, but it is lower than 8 years as the internationally used age limit for precocious puberty. [1,2] However, the Lawson Wilkins Pediatric Endocrine Society recently issued new recommendations for the age at which puberty should be considered precocious, lowering the prevailing standards from 8 years to 7 years for white girls and to 6 years for black girls.…”
Section: Original Articlesupporting
confidence: 90%
See 2 more Smart Citations
“…We used the 3rd percentile which is close to the usual cut-off measure of -2SD. In our study, the 3rd percentile for B2 is close to that reported by Razzaghi-Azar et al in Tehran, [7] and the age of precocious puberty is also very close to theirs, but it is lower than 8 years as the internationally used age limit for precocious puberty. [1,2] However, the Lawson Wilkins Pediatric Endocrine Society recently issued new recommendations for the age at which puberty should be considered precocious, lowering the prevailing standards from 8 years to 7 years for white girls and to 6 years for black girls.…”
Section: Original Articlesupporting
confidence: 90%
“…[6] We found higher ages for B2 and PH2 in girls mostly of Persian ethnicity in comparison to studies conducted in other parts of Iran, which included minority ethnicities in addition to Persians. The mean age at onset of menarche in Iranian girls living in the south Iran where has populations of Arab and Mazandaran ethnicities including Gilaki and Mazandarani ethnicities and the median age at menarche in girls living in Tehran where has different ethnicities such as Persian, Azeri, Gilaki and Mazandarani, Kurd, Arab and others are reported 12.91±1.23 years, [6] 12.68 (11.27-15.96) [7] and 12.5 years (12.4-12.5). [8] The girls in our study were mostly Persian, their ages at menarche were similar to those of girls of other ethnicities from other parts of Iran.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…O IMC (Índice de Massa Corporal) (5,6), torna-se variável fundamental na avaliação do crescimento, porém a mesma tem sido analisada em relação à idade cronológica, gerando uma perda de seu poder explicativo, já que nesta etapa da vida a idade biológica torna-se um parâmetro mais fidedigno (7,8).…”
unclassified
“…Para uma melhor análise do estado em que se encontram os adolescentes torna-se necessária à avaliação maturacional (5), e, dentre as muitas formas existentes, a maturação esquelética é o método clinicamente mais efetivo e prático (6), além de ser o mais fidedigno para se avaliar a idade biológica (7).…”
unclassified